EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN PROJECT BASED LEARNING DITINJAU DARI KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATA PELAJARAN IPAS KELAS 4 SEKOLAH DASAR - Arinda Octaviani, Theresia; Mawardi, Mawardi (Dharmas Education Journal (DE_Journal), 2024)
The purpose of this research is to determine the effectiveness of the Problem Based Learning and Project Based Learning models in terms of critical thinking skills in grade 4 elementary school science subjects. This research was carried out in the 4th grade at Gugus Gajah Mada Elementary School. The subjects in this research were SDN Dukuh 03 with 26 students, SDN Dukuh 05 with 20 students, and SDN Kecandran 01 with 28 students. The type of research design is a quasi-experimental Nonequivalent Control Group design. The data collection instrument uses a critical thinking skills rubric. Hypothesis testing is carried out using the t-test. Based on the results of data analysis, there are significant differences between experimental group 1 which applies the PBL model and experimental group 2 which applies the PjBl model. The prerequisite test results show that the data is normally distributed and homogeneous. The difference in the average value of critical thinking skills in the Problem Based Learning model is 74 and the Project Based Learning model is 79.92. So it can be interpreted that the Project Based Learning model is more effective than the Problem Based Learning model in terms of critical thinking abilities. The final results of calculations using the t test obtained a sig (2-tailed) value of 0.002 < 0.05, so Ho was rejected and Ha was accepted, so there is a difference between the use of Problem Based Learning and Project Based Learning models in terms of critical thinking skills in science subjects. 4th grade elementary school.